Honeycomb-like biomimetic scaffold by functionalized antibacterial hydrogel and biodegradable porous Mg alloy for osteochondral regeneration - Zhang, Yongqiang; Dong, Qiangsheng; Zhao, Xiao; Sun, Yuzhi; Lin, Xin; Zhang, Xin; Wang, Tianming; Yang, Tianxiao; Jiang, Xiao; Li, Jiaxiang; Cao, Zhicheng; Cai, Tingwen; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: Osteochondral repair poses a significant challenge due to its unique pathological mechanisms and complex repair processes, particularly in bacterial tissue conditions resulting from open injuries, infections, and surgical contamination. This study introduces a biomimetic honeycomb-like scaffold (Zn-AlgMA@Mg) designed for osteochondral repair. The scaffold consists of a dicalcium phosphate dihydrate (DCPD)-coated porous magnesium scaffold (DCPD Mg) embedded within a dual crosslinked sodium alginate hydrogel (Zn-AlgMA). This combination aims to synergistically exert antibacterial and osteochondral integrated repair properties. Methods: The Zn-AlgMA@Mg scaffold was fabricated by coating porous magnesium scaffolds with DCPD and embedding them within a dual crosslinked sodium alginate hydrogel. The structural and mechanical properties of the DCPD Mg scaffold were characterized using scanning electron microscopy (SEM) and mechanical testing. The microstructural features and hydrophilicity of Zn-AlgMA were assessed. In vitro studies were conducted to evaluate the controlled release of magnesium and zinc ions, as well as the scaffold’s osteogenic, chondrogenic, and antibacterial properties. Proteomic analysis was performed to elucidate the mechanism of osteochondral integrated repair. In vivo efficacy was evaluated using a rabbit full-thickness osteochondral defect model, with micro-CT evaluation, quantitative analysis, and histological staining (hematoxylin-eosin, Safranin-O, and Masson’s trichrome). Results: The DCPD Mg scaffold exhibited a uniform porous structure and superior mechanical properties. The Zn-AlgMA hydrogel displayed consistent microstructural features and enhanced hydrophilicity. The Zn-AlgMA@Mg scaffold provided controlled release of magnesium and zinc ions, promoting cell proliferation and vitality. In vitro studies demonstrated significant osteogenic and chondrogenic properties, as well as antibacterial efficacy. Proteomic analysis revealed the underlying mechanism of osteochondral integrated repair facilitated by the scaffold. Micro-CT evaluation and histological analysis confirmed successful osteochondral integration in the rabbit model. Discussion: The biomimetic honeycomb-like scaffold (Zn-AlgMA@Mg) demonstrated promising results for osteochondral repair, effectively addressing the challenges posed by bacterial tissue conditions. The scaffold’s ability to release magnesium and zinc ions in a controlled manner contributed to its significant osteogenic, chondrogenic, and antibacterial properties. Proteomic analysis provided insights into the scaffold’s mechanism of action, supporting its potential for integrated osteochondral regeneration. The successful in vivo results highlight the scaffold’s efficacy, making it a promising biomaterial for future applications in osteochondral repair.